THEORETICAL PREREQUISITES FOR THE DEVELOPMENT OF METHODS FOR APPLYING EDUCATIONAL TASKS IN THE PROCESS OF TRAINING WOULD-BE DOCTORS IN SURGERY - Климанский, Руслан; Касрашвили, Григорий; Самойленко, Елена (SWorldJournal, 2022)
Nowadays the problem of preparation of a surgeon is one of the most important in modern medical education. The article outlines the place of surgery in this process and describes some ways to make teaching surgery more effective. Therefore, the purpose o